Prevalence of Gastrointestinal Parasites of Goats in and around Jabalpur, Madhya Pradesh - Lata, Kusum; Das, G; Kumbhakar, Nitesh; Saiyam, Rupanjali (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted to investigate the prevalence of gastrointestinal (GI) parasites of goats in and around Jabalpur. During 9 months of study period, out of 1675 faecal sample of goats examined, 1224 (73.07%) were found positive for different gastrointestinal parasites. The maximum prevalence recorded was of Strongyles (61.43%) followed by Coccidia (25.97%), Amphistomes (9.73%), Monieziaexpansa (8.66%), Trichuris spp. (2.03%), Strongyloides spp. (1.79%) and Fasciolagigantica (0.66%). When prevalence was compared in goats maintained at field and farm conditions, significantly higher infection (P<0.01) was observed at farm (85.90%) as compared to field (67.22%) conditions. The prevalence of gastrointestinal parasitism was found higher in adults (73.83%) in comparison to young goats (69.71%). Overall specific species prevalence showed strongyles infection was significantly higher (P<0.01) in adult (64.25%) as compared to young (48.86%) whereas Coccidia and Monieziaexpansa infection was observed significantly high in kids than adult goats. The seasonal prevalence of gastrointestinal parasites was found significantly higher (P<0.01) in Monsoon (81.20%) and post-monsoon (76.66%) as compared to spring and winter seasons.